Smart Strategy for Family Financial Planning in 2025 - Azizul Halim Fadly (Proceeding of The International Conference on Business and Economics, 2025)
The aim of this research is to develop an effective strategy for family financial planning by utilizing secondary data obtained through literature studies. In today's consumer-driven society, managing finances wisely is essential to avoid impulsive spending and achieve long-term financial stability. The study identifies several key strategies that families can adopt to improve their financial behavior and planning. These include: (1) creating a budget and following it with discipline, (2) applying the “24-hour postpone” rule to avoid impulsive purchases, (3) reducing exposure to advertising, (4) focusing on long-term financial goals, (5) evaluating monthly shopping habits, (6) learning from personal desires instead of condemning them, and (7) reducing debt gradually. By implementing these strategies consistently, families can build better spending habits, avoid excessive consumer behavior, and work towards more sustainable financial well-being. These insights serve as a practical guideline for financial literacy and behavior modification in everyday family life.